Characterization of the rat transforming growth factor alpha gene and identification of promoter sequences. - Blasband, A J (1990)
We have determined the complete nucleotide sequence of rat transforming growth factor alpha (TGF alpha) mRNA and characterized the six exons that encode this transcript. These six exons span approximately 85 kilobases of genomic DNA, with exons 1 to 3 separated by particularly large introns. What had previously been thought to represent a species-specific difference in the size of the TGF alpha precursor (proTGF alpha) is now shown to be due to microheterogeneity in the splicing of exons 2 and 3. This results from a tandem duplication of the acceptor CAG and gives rise to two alternate forms (159 and 160 amino acids) of the integral membrane precursor. Exon 6, which encodes the 3' untranslated region of TGF alpha mRNA, also encodes, on the opposite strand, a small (approximately 200-nucleotide) transcript whose sequence predicts an open reading frame of 51 amino acids. Expression of this latter transcript does not appear to be coregulated with that of TGF alpha mRNA. Primer extension and S1 nuclease analyses of authentic TGF alpha transcripts revealed two major and multiple minor 5' ends which span more than 200 base pairs of DNA in a G + C-rich region that lacks canonical CCAAT or TATA sequences. The 5' ends of six independently derived cDNAs localized to five different sites in this same region. Restriction fragments that overlap these transcription start sites and extend approximately 300 base pairs in the 5' direction faithfully promote transcription in vitro with HeLa cell nuclear extracts. In addition, they direct the expression of the bacterial chloramphenicol acetyltransferase gene in transient-transfection assays.